Phase 1 expansion cohort of ramucirumab plus pembrolizumab in advanced treatment-naive NSCLC - Herbst, Roy S.; Arkenau, Hendrik Tobias; Bendell, Johanna; Arrowsmith, Edward; Wermke, Martin; Soriano, Andres; Penel, Nicolas; Santana-Davila, Rafael; Bischoff, Helge; Chau, Ian; Mi, Gu; Wang, Hong; et al. (Journal of thoracic oncology, 2021)
Introduction - Data of first-line ramucirumab plus pembrolizumab treatment of programmed death-ligand 1 (PD-L1)-positive NSCLC (cohort E) are reported (NCT02443324). - Methods - In this multicenter, open-label phase 1a/b trial, patients received ramucirumab 10 mg/kg and pembrolizumab 200 mg every 21 days for up to 35 cycles. PD-L1 positivity was defined as tumor proportion score (TPS) greater than or equal to 1%. Exploratory NanoString biomarker analyses included three T-cell signatures (T-cell-inflamed, Gajewski, and effector T cells) and CD274 gene expression. - Results - Cohort E included 26 patients. Treatment-related adverse events of any grade occurred in 22 patients (84.6%). Treatment-related adverse events of grade greater than or equal to 3 were reported in 11 patients (42.3%); the most frequent was hypertension (n = 4, 15.4%). Objective response rate was 42.3% in the treated population and 56.3% and 22.2% for patients with high (TPS ≥ 50%) and lower levels (TPS 1%-49%) of PD-L1 expression, respectively. Median progression-free survival (PFS) in the treated population was 9.3 months, and 12-month and 18-month PFS rates were 45% each. Median PFS was not reached in patients with PD-L1 TPS greater than or equal to 50% and was 4.2 months in patients with PD-L1 TPS 1% to 49%. Median overall survival was not reached in the treated population, and 12-month and 18-month overall survival rates were 73% and 64%, respectively. Biomarker data suggested a positive association among clinical response, three T-cell signatures, CD274 gene expression, and PD-L1 immunohistochemistry. - Conclusions - First-line therapy with ramucirumab plus pembrolizumab has a manageable safety profile in patients with NSCLC, and the efficacy signal seems to be strongest in tumors with high PD-L1 expression.
Available online 15 October 2020
Gesehen am 12.05.2021